Treatment of uncomplicated multidrug-resistant falciparum malaria with artesunate-atovaquone-proguanil. - van Vugt, M; Leonardi, E; Phaipun, L; Slight, T; Thway, K; Mcgready, R; Brockman, A; Villegas, L; Looareesuwan, S; White, N; Nosten, F (2002)
In an open-label trial carried out on the northwest border of Thailand, 1596 patients with uncomplicated multidrug-resistant falciparum malaria were randomly assigned to receive atovaquone-proguanil, atovaquone-proguanil-artesunate, or artesunate-mefloquine and were followed up for 42 days. All 3 regimens were highly effective and well tolerated. Fever duration and parasite clearance times were significantly shorter among patients who received artesunate (P<.001). Polymerase chain reaction genotyping confirmed that recrudescence occurred in 13 patients who received artesunate-mefloquine (2.4%), 5 who received atovaquone-proguanil-artesunate (0.9%), and 15 who received atovaquone-proguanil (2.8%). Adding artesunate to atovaquone-proguanil reduced the risk of failure 3-fold (95% confidence interval [CI], 1.1-8.2) and subsequent gametocyte carriage 21-fold (95% CI, 14-30). Gastrointestinal complaints in the first 48 h after initiation of treatment were more common among artesunate recipients, but after day 2, dizziness, sleep disturbance, nausea, vomiting, and anorexia were more common among mefloquine recipients (P< or =.014). Artesunate-atovaquone-proguanil is a highly effective and well-tolerated treatment for multidrug-resistant falciparum malaria.